Ответ(ы) на вопрос:
[latex] (2+\sqrt{3})^{x} +(2-\sqrt{3})^{x}\ \textless \ 3[/latex]
Так как [latex](2- \sqrt{3} )(2+ \sqrt{3} )=1[/latex], то справедливо соотношение:
[latex](2-\sqrt{3})=(2+\sqrt{3})^{-1}[/latex]
Поэтому [latex](2+\sqrt{3})^{x}+(2+\sqrt{3})^{-x}\ \textless \ 3[/latex]
Пусть [latex](2+\sqrt{3})^{x}=t[/latex]>0. Тогда
[latex]t+ \frac{1}{t} \ \textless \ 3[/latex]
[latex] \frac{t^{2}-3t+1}{t} \ \textless \ 0[/latex]
Найдем корни числителя.
[latex]D=(-3)^{2}-4*1*1=5[/latex]
[latex]t_1= \frac{3- \sqrt{5} }{2}[/latex]
[latex]t_1= \frac{3+ \sqrt{5} }{2}[/latex]
[latex] \frac{(t- \frac{3-\sqrt{5}}{2} )(t- \frac{3+\sqrt{5}}{2} )}{t} \ \textless \ 0[/latex]
Так как t>0, [latex](t- \frac{3-\sqrt{5}}{2} )(t- \frac{3+\sqrt{5}}{2} )\ \textless \ 0[/latex]
t∈[latex](\frac{3-\sqrt{5}}{2};\frac{3+\sqrt{5}}{2})[/latex]
Тогда x∈[latex](log_{2+\sqrt{3}}(3-\sqrt{5});log_{2+\sqrt{3}}(3+\sqrt{5}))[/latex]
Не нашли ответ?
Похожие вопросы